1968
DOI: 10.1128/jb.95.2.520-530.1968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nalidixic Acid and Hydroxyurea on Division Ability ofEscherichia coli fil+andlonStrains

Abstract: Short periods of incubation in medium containing nalidixic acid or hydroxyurea, followed by a return to normal growth conditions, induced filament formation in Escherichia coli B (fil+) and AB1899NM (Ion-) but not in B/r (fil-) and AB1157 (lon+). These drugs reversibly stopped deoxyribonucleic acid (DNA) synthesis with little or no effect on ribonucleic acid (RNA) synthesis or mass increase. The initial imbalance caused by incubation in these drugs was the same for B and B/r as was macromolecular synthesis fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…S1 A-G). Residual nalidixic acid is unlikely to contribute to the ROSmediated killing on agar, because quinolone-gyrase-DNA complexes are reversible, and washing cells to remove quinolone fully restores DNA synthesis blocked by formation of the complexes (31)(32)(33); if the complexes are rendered irreversible by crosslinking of quinolone to gyrase, DNA synthesis is not restored (32). In addition, a mass spectrometry-based assay showed that washing and diluting cells lowered intracellular quinolone concentration to 0.002 times MIC (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1 A-G). Residual nalidixic acid is unlikely to contribute to the ROSmediated killing on agar, because quinolone-gyrase-DNA complexes are reversible, and washing cells to remove quinolone fully restores DNA synthesis blocked by formation of the complexes (31)(32)(33); if the complexes are rendered irreversible by crosslinking of quinolone to gyrase, DNA synthesis is not restored (32). In addition, a mass spectrometry-based assay showed that washing and diluting cells lowered intracellular quinolone concentration to 0.002 times MIC (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This compound, or a closely related derivative, probably also acts in the regulation of cell division (9). Both prophage induction and cell division seem to be intimately related to some phase of the DNA replication cycle (2,8).…”
Section: Discussionmentioning
confidence: 99%
“…When the nalidixic acid concentration is above the minimum inhibitory concentration (MIC), DNA synthesis is blocked. However, promptly after the nalidixic acid is washed away, DNA synthesis resumes (12). Based on mass spectrometry quantification, Hong et al (10) measure a decrease in intracellular nalidixic acid concentration to 0.002 MIC after washing and diluting treated cells.…”
Section: Time After Addition Of Antibioticmentioning
confidence: 99%